Eosinophilic Peritonitis Associated with Peritoneal Dialysıs Fluid Containing Low Concentration of Degradation Products - Yılmaz, Kenan; Dursun, İsmail; Yel, Sibel; Gündüz, Zübeyde; Sunkak, Süleyman (Fırat University, 2013)
A 17-year-old boy with end-stage renal disease secondary to hyperoxaluria who had been on continuous ambulatory peritoneal dialysis for 6 months was admitted to our hospital for evaluation of a cloudy dialysate without abdominal pain and fever. He was diagnosed as eosinophilic peritonitis. Eosinophilic peritonitis (EP) is hypersensitivity reaction of the peritoneal membrane due to variety of allergens during peritoneal dialysis. It is a frequently underestimated problem since it seems bacterial peritonitis that emerges with cloudy dialysate. Our aim in this report to emphasize that EP may occur in patients using fluids with low concentrations of degradation products (1.5% glucose solution) and to raise awareness of EP.

Hiperoksalüriye ikincil son dönem böbrek yetmezliği nedeniyle 6 aydır sürekli ayaktan periton diyalizi yapılan 17 yaşındaki erkek hasta karın ağrısı ve ateş olmaksızın bulanık diyalizat sebebiyle hastanemize kabul edildi. Eozinofilik peritonit teşhisi konuldu. Eozinofilik peritonit (EP) periton diyalizi tedavisi sırasında çeşitli alerjenlere bağlı ortaya çıkan periton zarındaki hipersensitivite reaksiyonudur. Bakteriyel peritonitler gibi periton sıvısında bulanıklık ile ortaya çıktığından sıklıkla gözden kaçabilen bir problemdir. Olguyu sunma amacımız, düşük glikoz yıkım ürünü içeren diyaliz sıvısı (%1.5 glukoz solüsyonu) ile de EP gelişebileceğini vurgulamak ve EP farkındalığını artırmaktır.
Düşük Glukoz Yıkım Ürünü İçeren Diyaliz Sıvısı ile İlişkili Eozinofilik Peritonit